Beaming Terahertz waves : a negative gradient-index meta-surface for out-coupling of surface propagating waves - Peh, Rui Jie (2016)
A broadband Surface-to-Plane wave out-coupler was designed and simulated to couple surface propagating wave into x-polarized plane wave at 3 THz. The out-coupler is a periodically structured negative gradient-index meta-surface with each unit cell comprising of numerous H-shaped sub cells that are subwavelength along the in-plane dimensions. The negative gradient-index meta-surface is advantageous to second-order Bragg grating for surface emission due to its broadband characteristics. This is possible due to the change in phase response that is caused by the shift in the resonance of the H-shaped sub cell as the operating frequency of the surface wave changes. Furthermore, as the H-shaped sub cells only scatter x-polarized electromagnetic waves, the out-coupler does not suffer from coupling losses to orthogonal polarizations. And through conservation of wave vector, the direction of propagation can be controlled by engineering the phase gradient of a unit cell. A generalized expression for the angle of propagation (Polar angle) was derived for a one-dimensional (1-D) gradient-index meta-surface. And the simulated results agree with good consistency with the generalized expression despite showing slight deviations that can be attributed to the non-uniform scattering amplitude of each H-shaped sub cell. Thus these results open up possibilities for dynamic two-dimensional (2-D) Beamforming and Beam steering in the Terahertz spectrum.